TRACHEO-CUTANEOUS FISTULA: A RARE PRESENTATION DUE TO A FORGOTTEN RUBBER BAND IN NECK OF A YOUNG GIRL - Amna Ikram,; Idrees, Amna; Somia Ilyas,; Sikandar Ali,; Muhammad Ali Shiekh, (Journal of Ayub Medical College Abbottabad, 2022)
The presence of foreign bodies in a chronic wound is a well-known phenomenon. The common locations are wrist, neck and chest cavity. Retained foreign bodies in soft tissues become reason for formation of sinus which can be superimposed by infection. Most of foreign bodies in soft tissues remain un-detected, becoming the reason for delayed diagnosis. Some of the foreign bodies are inert and stay in the body tissues for prolonged time without causing any deleterious effect but few of them erode into surrounding tissues and cause prolonged illness. Tracheo-cutaneous fistula secondary to a foreign body in a child is rarely reported. In this case, the patient had retained foreign body in her neck for almost eight years which remained un-diagnosed while being treated for various diseases.